Deskripsi Keterlaksanaan Proses Pembelajaran Pendidikan Kewarganegaraan (PKn) di Kelas IV SDN 38 Pontianak Utara Menggunakan Kurikulum Merdeka - Jumiadi Firmansyah; Dyoty Auliya Vilda Ghasya; Rio Pranata (Journal on Education, 2024)
The purpose of this study was to describe the implementation of the learning process and the obstacles faced by teachers in learning the Merdeka curriculum in class IV of SDN 38 North Pontianak. This research uses a qualitative descriptive method. The results of this study are the implementation of Merdeka curriculum learning in class IV, and the obstacles faced by teachers in implementing Merdeka curriculum learning. Researchers obtained results from interviews with class IV teachers in interviewing implementation, observation of implementation and obstacles faced by teachers in learning the Merdeka curriculum and observation in class IV obtained by observing class IV teachers at SDN 38 North Pontianak.